Effect of topology on quasiparticle interactions in the Weyl semimetal WP2 - Wulferding, Dirk; Lemmens, Peter; Buescher, Florian; Schmeltzer, David; Felser, Claudia; Shekhar, Chandra (Physical Review B, 2020)
We compare two crystallographic phases of the low-dimensional WP2 to better understand features of electron-electron and electron-phonon interactions in topological systems. The topological β phase, a Weyl semimetal with a giant magnetoresistance, shows a larger intensity of electronic Raman scattering compared to the topologically trivial α phase. This intensity collapses for T<T∗=20K, which evidences a crossover in the topological phase from marginal quasiparticles to a coherent low-temperature regime. In contrast, the topologically trivial α phase shows more pronounced signatures of electron-phonon interaction, i.e., an enhanced phonon linewidth and deviations from conventional anharmonicity in an intermediate-temperature regime. These effects provide evidence for an interesting interplay of electronic correlations and electron-phonon coupling. Interband and intraband electronic fluctuations can be distinguish by the energy range of electronic Raman scattering and their temperature dependence. Furthermore, we demonstrate a decisive dependency on symmetry that is critical to understand their interplay.
CRIS-Team Scopus Importer:2022-04-14